Novel small molecules that increase the susceptibility of Neisseria gonorrhoeae to cationic antimicrobial peptides by inhibiting lipid A phosphoethanolamine transferase. (30th June 2022) - Mullally, Christopher; Stubbs, Keith A; Thai, Van C; Anandan, Anandhi; Bartley, Stephanie; Scanlon, Martin J; Jarvis, Gary A; John, Constance M; Lim, Katherine Y L; Sullivan, Courtney M; Sarkar-Tyson, Mitali; Vrielink, Alice; et al.
Abstract: Objectives: Neisseria gonorrhoeae is an exclusively human pathogen that commonly infects the urogenital tract resulting in gonorrhoea. Empirical treatment of gonorrhoea with antibiotics has led to multidrug resistance and the need for new therapeutics. Inactivation of lipooligosaccharide phosphoethanolamine transferase A (EptA), which attaches phosphoethanolamine to lipid A, results in attenuation of the pathogen in infection models. Small molecules that inhibit EptA are predicted to enhance natural clearance of gonococci via the human innate immune response. Methods: A library of small-fragment compounds was tested for the ability to enhance susceptibility of the reference strain N. gonorrhoeae FA1090 to polymyxin B. The effect of these compounds on lipid A synthesis and viability in models of infection were tested. Results: Three compounds, 135, 136 and 137, enhanced susceptibility of strain FA1090 to polymyxin B by 4-fold. Pre-treatment of bacterial cells with all three compounds resulted in enhanced killing by macrophages. Only lipid A from bacterial cells exposed to compound 137 showed a 17% reduction in the level of decoration of lipid A with phosphoethanolamine by MALDI-TOF MS analysis and reduced stimulation of cytokine responses in THP-1 cells. Binding of 137 occurred with higher affinity to purified EptA than the starting material, as determined by 1D saturation transfer difference NMR. Treatment of eight MDR strains with 137 increased susceptibility to polymyxin B in all cases. Conclusions: Small molecules have been designed that bind to EptA, inhibit addition of phosphoethanolamine to lipid A and can sensitize N. gonorrhoeae to killing by macrophages.